DESKRIPTIF LITERATUR REVIEW DISKRIMINASI PENYANDANG DISABILITAS DALAM DUNIA KERJA - Zira Aura Sekarini; Hastin Trustisari (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Background: Getting a decent job is the right of every individual, regardless of social status. In Indonesia, this is regulated in Article 27 Paragraph 2 of the 1945 Constitution which states that